"The boob answers a lot of problems": Exploring barriers and enablers to successful extended breastfeeding in women with high BMIs. (2020) - O'Reilly, Sharleen; O'Brien, Eileen; Walker, Hannah; O'Carroll, Eimear; Courtney, Joanne; McAuliffe, Fionnuala
Abstract: Introduction: Breastfeeding provides optimal nutrition for infants yet breastfeeding rates worldwide do not meet WHO targets for 50% exclusive breastfeeding at 6 months. Ireland's breastfeeding rate is one of the lowest in the world (only 58% initiation) and maternal obesity and overweight is prevalent (> 50% pregnancies). Women with obesity and overweight are particularly at risk of having lower breastfeeding rates but little is known about the factors that supported this sub-group to successfully breastfeed. Our aim was to explore barriers and enablers present in: women with high body mass index (BMI) who successfully breastfed for > 6 months, partners of women with > 6 months breastfeeding, and healthcare professionals (HPs) who support women to breastfeed. Materials and Methods: Women with high BMIs (n = 20) were recruited via an extended breastfeeding Facebook group and snowballing. Partners (n = 20) were recruited via social media and word of mouth. HPs (n = 19) were recruited via posters and direct invitation. Semi-structured interviews were conducted either in-person or on telephone and digitally recorded. Interviews were verbatim transcribed and thematically analysed. Two research students independently coded each interview and consensus decided any discrepancies. Results: Barriers to breastfeeding identified aligned with previous research but the challenges appear to be increased for either the frequency or intensity of occurrence in women with high BMIs. Common barriers are: a lack of breastfeeding culture; limited access within health services to high quality and consistent breastfeeding advice; large breast size; and issues with breastfeeding in public. Enablers for successful extended breastfeeding are: strong self-efficacy; supportive partner and family; social networks for creating breastfeeding-friendly settings; seeking support from a lactation consultant; and breastfeeding aides (clothing, pillows, lanolin, etc.). Discussion: Women with high BMIs are able to successfully breastfeed for extended periods of time when they are provided with the right support at the right time and in a way that is acceptable to them and their families. Reorientation of maternity health services to ensure greater and more consistent support for women with high BMIs to initiate breastfeeding is needed. HPs engaging with women with high BMIs should seek to support them through the use of the enablers identified and make a conscious decision to include appropriate advice for women with high BMIs in their antenatal education and any postpartum services provided.